Appreciation of facial features: comparison between mathematical evaluation and human perspective on female aesthetical judgemants - Wong, Peggy Bik Kee (2006)
Golden Section, holding the proportion of I: 1.618 is claimed as one of the most numerically beautiful linear proportions and serves as a famous the "formula of beauty" in a mathematical sense. The Golden Section is developed by taking the ratio between the two successive numbers in Fibonacci series with the first number being the denominator and the latter being the numerators. The Golden Mask claimed that any face which could fit the mask can be considered as a beautiful face and it is universally acceptable regardless of ethnics. The main objective of this study is to compare mathematical evaluation against human perspective on aesthetical judgements within the variables of sex and ethnics. Data for this study were collected from 200 respondents from the School of Science and Technology, Universiti Malaysia Sabah. Two statistical tests were used, namely Two-Tailed T-Test, Independent T Test and One-Way ANOV A. The results obtained show that males and females share the same opinion regarding beauty and there is no difference in term of human perspectives when judging the facial aesthetics of different ethnics. The result also show that there is clean difference between mathematical evaluation and human perspective on facial aesthetical judgement. Furthermore, the Correlation coefficient analysis shows that there is no relationship between facial elements and facial beauty. Therefore, it can be concluded that "beauty is universal" and it adheres to follows the golden proportion.